Chronic miR‐29 antagonism promotes favorable plaque remodeling in atherosclerotic mice - Victoria Ulrich; Noemi Rotllan; Elisa Araldi; Amelia Luciano; Philipp Skroblin; Mélanie Abonnenc; Paola Perrotta; Xiaoke Yin; Ashley Bauer; Kristen L Leslie; Pei Zhang; Binod Aryal; et al. (EMBO Molecular Medicine, 2016)
Abstract Abnormal remodeling of atherosclerotic plaques can lead to rupture, acute myocardial infarction, and death. Enhancement of plaque extracellular matrix (ECM) may improve plaque morphology and stabilize lesions. Here, we demonstrate that chronic administration of LNA‐miR‐29 into an atherosclerotic mouse model improves indices of plaque morphology. This occurs due to upregulation of miR‐29 target genes of the ECM (col1A and col3A) resulting in reduced lesion size, enhanced fibrous cap thickness, and reduced necrotic zones. Sustained LNA‐miR‐29 treatment did not affect circulating lipids, blood chemistry, or ECM of solid organs including liver, lung, kidney, spleen, or heart. Collectively, these data support the idea that antagonizing miR‐29 may promote beneficial plaque remodeling as an independent approach to stabilize vulnerable atherosclerotic lesions.